2016
DOI: 10.4236/oalib.1102809
|View full text |Cite
|
Sign up to set email alerts
|

Khat Chewing Induces Cardiac Arrhythmia

Abstract: Background: Khat is a natural stimulant from the Catha edulis plant containing several chemical components, which can explain palpitation as a frequent symptom that develops during or after khat chewing. Aims: To study the effects of khat chewing on cardiac rhythm. Methods: We selected sixty khat-chewing Yemeni individuals and divided them into two groups: 30 were cardiac patients and the other 30 were non-cardiac individuals. All 60 individuals underwent 24 hours holter monitoring for 2 consequent days; the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
(10 reference statements)
1
8
0
Order By: Relevance
“…In addition, the present study showed that khat chewing has no significant association with CA (p=0.652). In an argument with our study findings, a study conducted in Yemen in 2016 found that the prevalence of non-sustained ventricular tachycardia was higher among khat chewers 39 . The possible difference is that majority of the participants in our study were women (who do not culturally encourage to chew khat than men).…”
Section: Discussionsupporting
confidence: 79%
“…In addition, the present study showed that khat chewing has no significant association with CA (p=0.652). In an argument with our study findings, a study conducted in Yemen in 2016 found that the prevalence of non-sustained ventricular tachycardia was higher among khat chewers 39 . The possible difference is that majority of the participants in our study were women (who do not culturally encourage to chew khat than men).…”
Section: Discussionsupporting
confidence: 79%
“…The cardiovascular changes, induced by chewing khat, show evidence of a significant rise in arterial systolic and diastolic blood pressure and pulse rate with a peak effect of three hours after starting chewing khat. These changes run parallel with the changes in plasma Cathinone levels during and after khat chewing [4]. Regular chewing of Khat is associated with elevated mean diastolic blood pressure, which is consistent with the peripheral vasoconstrictor effect of Cathinone [6].…”
Section: Theoretical Background and Statement Of The Problemmentioning
confidence: 56%
“…Khat or Catha edulis is an indigenous plant in Yemen, Ethiopia and East Africa, which has sympathomimetic and euphoriant effects [4]. The phenylpropylamine-type alkaloid cathinone is the major component responsible for the effects of khat on the heart and blood vessels.…”
Section: Theoretical Background and Statement Of The Problemmentioning
confidence: 99%
“…A significant difference was also seen among the normal individuals; one patient (3.3%) developed VT's short runs on a khat-chewing day than non-VT on a khat-free day. Serious arrhythmias occur in cardiac and non-cardiac individuals during khat chewing days, although they are more prominent among cardiac patients [ 25 ]. However, further studies are needed regarding khat’s effects on cardiac rhythm.…”
Section: Reviewmentioning
confidence: 99%